(untitled) (Tzintzun, Revista de Estudios Históricos, 2019)
This paper examines how the newspaper La Voz de Michoacán has changed the way it refers to a sector that has been little analyzed by Mexican historiography: the deaf. The role of the press, in dissemination and modification of people’s opinion and perspective about this community, is highlighted through analyzing documents related to deaf people, and contextualizing these manuscripts into processes as rehabilitative medical model implementation, subsequently emphasizing human rights and non-discrimination to hearing-impaired people in Morelia.